From blunt to cutting: Distinguishing alternating method flakes in early stages on rounded blanks. (8th August 2016) - Guardiola, M.; Morales, J.I.; Vergès, J.M.
Abstract: Two main knapping strategies can be used to start bifacial reduction on a lithic cobble or nodule: the alternate strategy, in which first one face is knapped and then the other; and the alternating strategy, in which both faces are removed in the same sequence, interspersing core about-turns between strikes. Flaking reduction of spherical and elliptical blanks (cobbles or nodules) is a common knapping process documented in many archaeological records. Rounded and thick edges require different fracture parameters and give rise to constraints in terms of viable knapping methods. When analysing abandoned cores, it is only possible to see the last strikes, so it is important to know how they were shaped or exploited in the earlier knapping stages in order to understand the entire reduction process. As cortical flakes are the direct evidence of the first reduction phases, we undertook an experimental programme for the purpose of comparing the first flakes generated using the alternate and alternating knapping strategies. We have focused our efforts on identifying and diagnosing distinctive features produced by each strategy in the first or cortical flakes. Our study indicates that several platform attributes can be considered as diagnostic features to differentiate between the alternate and alternating knapping strategies, and that this kind of analysis can be translated to archaeological assemblages.